Tradução e adaptação transcultural do adolescent asthma self-efficacy questionnaire e asthma knowledge questionnaire para o português do Brasil e análise de suas propriedades de medida - Berdu, Nathalia Ribeiro (2022)
Introduction: Some scales assess the self-efficacy of asthmatics, but do not take into account issues related to age and the use of correct medications. Objective: To translate, adapt cross-culturally to the Portuguese and test the measurement properties of the Adolescent Asthma Self-Efficacy Questionnaire (AASEQ) and the Asthma Knowledge Questionnaire (AKQ) for use in adolescents with asthma and in their parents/caregivers. Methods: The questionnaires were translated and adapted for the Portuguese. Its final versions were applied in two moments with an interval between seven and fourteen days. Reliability, agreement, construct validity and ceiling and floor effect were evaluated. Results: 135 adolescents (age 14 (age 12 – 16)) were evaluated, and the severity of mild asthma was evaluated in 63 (46.6%), with controlled symptoms in 90 (66.7%). The internal consistency of AASEQ and AKQ were substantial (Cronbach's alpha 0.70 and 0.73 respectively). The standard error of measurement was very good (SEM = 5.82 points and DMD90% = 6.68 points in the AASEQ, EPM = 2.65 points and DMD90% = 4.51 points in the AKQ), showing moderate reliability in the AASEQ ( ICC3.1: 0.68 [95% CI: 0.55 - 0.77], p<0.0001) and in the AKQ (CCI3.1: 0.72 [95% CI: 0.57 - 0.81], p<0.0001). The construct validity of the AASEQ was weak with the PedsQL (r= 0.28 and p < 0.05) and with the PAQLQA (r= 0.27 and p>0.05). The floor and ceiling effect were adequate in both questionnaires. Conclusion: The AASEQ and the AKQ are reliable tools for use in asthmatic adolescents and their caregivers.